Optimization and sustainability analysis of PV/wind/diesel hybrid energy system for decentralized energy generation. (November 2020) - Nsafon, Benyoh Emmanuel Kigha; Owolabi, Abdulhameed Babatunde; Butu, Hemen Mark; Roh, Jong Wook; Suh, Dongjun; Huh, Jeung-Soo
Abstract: This paper focuses on the techno-economic feasibility and sustainability of a PV/wind/diesel hybrid system designed for decentralized power supply. Several designs have been studied for the hybrid system by varying the PV slope and wind turbine hub height under different dispatch strategies to supply the load. For each design, the power system has been optimized to determine the maximum electrical output at a low cost. Sensitivity analyses have been performed to evaluate operational risk in the actual operation as well as the cost-effectiveness of the proposed system. As a final remark, the sustainability of the proposed hybrid energy system has been analyzed based on some key indicators to understand the implications of a design choice on electrical production, CO2 emission and cost of energy. Our results show that for a projected period of 25 years, the selected hybrid power system for electrification of a housing estate will cost 10.2 million USD for a daily load of 4876.5 kWh, and the cost for every kWh of electricity generated is 0.4574. Results also show that the hybridization of the standard diesel generating system increased the reliability and cost-effectiveness of the power system, saving 0.316 for every kWh of electricity generated, with about 1, 521, 310 kg of CO2 emission avoided annually. Highlights: Hybridization and optimization of the design configuration increased the efficiency of the power system. Sustainable energy indicators are applied to analyse a hybrid energy system for a housing estate. Effects of PV slope, wind turbine hub height and dispatch strategy on total electrical production and CO2 emission are analysed. The COE achieved in the hybrid system is very promising for the study area.